Evaluation of Ramie Bark and Albasia Sawdust Substrates for Mycelium-Based Composites Using Leiotrametes lactinea - Wulandari, Asri Peni; Sukmana, Dwi Ramadhani; Kusumah, Sukma Surya; Fadillah, Muhammad Nugraha; Abdul Rohmat (Journal of Fibers and Polymer Composites, 2024)
Mycelium-based composite (MBC) has significant potential to utilize agricultural biomass waste. The use of fungi that are commonly used as MBC materials is still very limited to certain types. This study aims to test the MBC characteristics of the growth of mycelium Leiotrametes lactinea MYCL-3 on three different media substrates containing 72% Albasia (SA) sawdust, 72% ramie bark (BR), and 30% Albasia + 47% ramie mixture (SA-RB). The resulting MBC has dimensions of 20 x 5 x 5 cm and is yellowish-white in color. The structure of MBC shows that the density is higher (BR 0.28%). The absorption percentages for SA, RB, and SA-RB were 28.66, 21.37, and 27.22, respectively. The biodegradability of MBC showed that by day 10, the sample had degraded by about 14.14–17.46%. Mechanical testing for compression strength determined values for SA (117 kPa), RB (350 kPa), and SA-RB (140 kPa), with a final strength at 464 kPa, and the effect of the mixed media reduced the tensile strength of the composite to 277 kPa. The IR spectral results showed that the three composite samples did not show much different structures, but SA composites were known to have more types of constituent compounds not found in BR and SA-RB composites such as C=C (alkenes) bending, O-H (alcohol) associations, C-O-C (glycosidic) stretching, O-H (acid) bending, and C=C (benzene) stretching. Future investigations may focus on improving aggregate interlocking to increase strength and flexibility, tailoring MBC for specific applications.